Microplastic Contamination in Drinking Water: A Review - Abdul Rahman; Ramadhan Tosepu; Surya Cipta Ramadhan Kete; Asnia Zainuddin; Mubarak; Ranno Marlany Rachman (Journal of Health Science and Pharmacy, 2025)
Background: Microplastics are plastic particles smaller than 5 µm that persist in the environment and resist natural degradation. Recent studies have demonstrated the presence of microplastics in various environmental media, including drinking water. This contamination raises public health concerns because microplastics can enter the human body through daily water consumption and may carry hazardous chemical substances, potentially causing long-term health effects. Objective: This study aims to examine the presence, characteristics, and potential health risks of microplastic contamination in drinking water through a systematic literature review. Method: A Systematic Literature Review (SLR) was conducted following the PRISMA guidelines. Scientific articles were obtained from Google Scholar, ResearchGate, PubMed, Scopus, and ScienceDirect using the keywords microplastic, drinking water, bottled water, and health risk. Data were analyzed descriptively, focusing on microplastic types, particle sizes, polymer composition, and identification methods. Results: Microplastics were detected in bottled water, refill drinking water, and tap water in several countries, including Indonesia. The dominant forms were fragments and fibers, with sizes ranging from 0.01 µm to >5 µm. The most common polymers were polyethylene terephthalate (PET), polypropylene (PP), polyethylene (PE), and polystyrene (PS). Identification methods included filtration, microscopy, ATR-FTIR, Raman spectroscopy, and SEM-EDS. Potential health risks include inflammation, oxidative stress, digestive disorders, and carcinogenic effects. Conclusion: Microplastics are confirmed contaminants in drinking water and may pose risks to public health. Strengthened monitoring, standardized detection methods, improved water treatment technologies, and public awareness are essential to reduce exposure.